HUBUNGAN PENERAPAN SEKOLAH LAPANG â€œSRI-ORGANIKâ€ UNTUK KEMANDIRIAN PETANI BERWAWASAN AGRIBISNIS - SUSWADI SUSWADI; MAHANANTO MAHANANTO (JURNAL ILMIAH AGRINECA, 2014)
Boyolali is one of the Rice Granary and the National Central Java, because its results could be sufficient paddy rice for the Boyolali and there is a surplus of more than 64,000 tons of paddy / her year, but with climate change makes the rainy and dry seasons are not clearly came from. This resulted in a decrease in rice production up to 10-20% so that endanger regional and national food security. Farmers have only depend on the government for assistance and solutions in solving the problem. While the government can address the lack of fast, could not give a good solution to the farmers. This can happen because the extension method that has been done only for the transfer of technology for solving problems that only a moment, and if there is a new problem, farmers can not do anything about it. Field School "SRI-Organic" is an extension method with a systematic process of participatory education to go forward with vision agribusiness farmers, the farmers are able to opt into a farming system that is more efficient in an effort to optimize production, market-oriented and able to compete. Able to make decisions independently in solving problems and not always rely on outsiders to deal with changing environmental circumstances, including climate change. Transfer of technology: SRI, Organic and ICS via method field schools will be able to solve the problems faced by farmers in a sustainable manner, because in addition to Field School results oriented mentoring process but also how the results are achieved. This regard to the success of this research aims to generate a model transformation system farmers who "depend" to the independent-minded farmers Agribusiness and integrated farming systems, so that in the first year there has been a change in an increase in the independence-minded farmer Agribusiness in the face of climate change so occurs: (a). increased production, (b). The increase in revenue, (c). Decrease the cost of farming. Â  Â